Difference in weight loss based on ethnicity, age and comorbidity status in a publicly funded adult weight management centre: 1‐year results. Issue 1 (22nd April 2013) - Liu, R. H.; Wharton, S.; Sharma, A. M.; Ardern, C. I.; Kuk, J. L.
Summary Limited evidence is available on the effectiveness of publicly funded weight loss (WL) clinics. We examined the 1‐year WL outcomes and investigated predictors of WL and discontinuation of 1566 overweight and obese adults, who attended the Wharton Medical Clinic (WMC) weight management centre for at least 6 months. Overall, 42.7% (n = 669) of the entire sample achieved a ≥5%WL over the entire follow‐up period from July 2008 to February 2012. On average, patients lost 5.6 ± 7.2 kg (5.0 ± 6.3%) of initial body weight (BW), while a subsample of patients attending the clinic for at least 1 year had a mean weight reduction of 6.6 ± 7.9 kg (5.9 ± 7.2%) of BW. Older patients were more likely to achieve a greater WL in comparison with young patients while White patients and those without type 2 diabetes (T2D) lost almost twice as much weight and %BW in comparison with Asian patients and patients with T2D, respectively (P < 0.05). Discontinuing patients did not differ in terms of sex, body mass index, education and smoking status from those who continued treatment (P > 0.05). Results of this study demonstrate that the WMC provides a practical model for clinically effective lifestyle‐based treatment, accessible to a wide range of demographically diverse adults.